The branch and bound algorithm for a backup virtual path assignment in survivable ATM networks - Walkowiak, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Issues of network survivability are important, since users of computer networks should be provided with some guarantees of data delivery. A large amount of data may be lost in high-speed Asynchronous Transfer Mode (ATM) due to a network failure and cause significant economic loses. This paper addresses problems of network survivability.
Keywords: survivable networks; ATM; branch and bound algorithm